Pengembangan Model Fun Painting untuk Meningkatkan Keterampilan Motorik Halus Anak TK B di Kota Bandar Lampung - Citra, Aulia Gustina (Martabat: Jurnal Perempuan dan Anak, 2017)
The objective of this research is to develop fine motor skills at TK B with Funpainting. The method used in the research is the research and development,developed by Borg and Gall. Development of the model used in this studyuses ASSURE: 1)Analyze Learner, 2)State objectives, 3)Select instructionalmethods, media and material, 4)Utilize media and material, 5)Requirelearner participation dan 6) Evaluate and revise. The purpose of this researchis to encourage kindergarten teachers, parents, and schools to facilitate theimplementation the model of Fun painting for young children. The techniqueof analysis data by using descriptive and qualitative. The model system toFun painting is consist of actions book and teachers planner.Keywords: Fine Motor Skills, Fun Painting, Research and Development